Study on intra-wave frequency modulation phenomenon in detection of rub-impact fault. (1st May 2019) - Zhou, Peng; Du, Minggang; Chen, Shiqian; He, Qingbo; Peng, Zhike; Zhang, Wenming
Highlights: A novel method named M-VNCMD is introduced to deal with the intra-wave FM signal. The intra-wave FM phenomenon in rubbing response is revealed and investigated. The relation between modulation pattern and spectrum of response is established. The superiority of diagnosing rubbing fault based on modulation law is verified. Abstract: The rub-impact fault occurring in the rotating machinery can cause the periodically frequency modulation (FM) in its vibration response. Such kind of modulation mode has been named as intra-wave FM effect, which carries the intrinsic fault information of rubbing-related dynamic system. Assisted by a fast-modulated instantaneous frequency (IF) extraction method named M-VNCMD, the intra-wave FM phenomena arising in several simulated and real rubbing responses are revealed and investigated in detail in this paper. To be specific, the intra-wave FM response is firstly modeled as the sinusoidal modulation form according to the extracted fault features, and then expanded as a series of harmonics to establish the relationship between its modulation pattern and Fourier spectrum. The connection among the fault diagnosis criteria based on modulation patterns and Fourier spectrum is finally uncovered to demonstrate the superiority of diagnosing the rubbing fault depending on modulation features.